Utilization, Credibility and Effectiveness of Communication Media among Bt Cotton Growers - U.R. Chinchmalatpure; H.D.Rajput; C.P.Girase (Journal of Agricultural Extension Management, 2025)
Cotton is a major cash crop of India. It is grown in varied agro-climatic situations across nine major states viz. Maharashtra, Gujarat, Madhya Pradesh, Punjab, Haryana, Rajasthan, Andhra Pradesh, Karnataka and Tamil Nadu.